The Applicability of CNPs Worksheet for Measuring Students’ Ability in Designing Experiment - Purwoko Haryadi Santoso; Yusman Wiyatmo (Kasuari: Physics Education Journal (KPEJ), 2020)
This developmental research had developed two applicablecurious note programs (CNPs) worksheets for quantifyingstudent performances in designing experiment on newton law’s of gravity. This study involved fourdevelopmental proceduresof Thiagarajan’s 4-D model. The CNPs worksheet was pilot tested in 3 groups of students at Yogyakarta’s public school. It included 22 students for the pilot group and 60 students for the implement group.  Our initial step of this developmental project had designed applicable CNPs worksheet based on acceptable CVI values, reliable measured results, and positivefeedbacks from the user in both worksheets. Using this instrument, this study had revealed some interesting findings that our participants still discovered some difficulties in performing this kind of scientific abilities. Meanwhile, this study has recommended CNPs worksheet for the physics education communities as a convincing tool for measuring students’ ability in designing physical experiment.